Development of Adobe flash-assisted interactive multimedia to improve sound symbol understanding and language skills - Yosepha Kurniawati Deze Say; Kastam Syamsi (JINoP (Jurnal Inovasi Pembelajaran), 2026)
Background: The effectiveness of interactive multimedia in language learning is not automatic. It is strongly influenced by pedagogical design, the alignment of content with students’ linguistic development, and integration with the applicable curriculum. Interactive multimedia that is not designed systematically may only increase learning engagement without producing a significant effect on deeper mastery of language skills. Objectives: This study aimed to develop Adobe Flash-assisted interactive multimedia for learning sound symbols and to examine its effectiveness in improving sound symbol understanding and language skills among first-grade elementary school students. Methods: The interactive multimedia was developed using the 4D model, which consists of Define, Design, Develop, and Disseminate. The product was validated by a media expert and a subject-matter expert. The research participants were first-grade students from the Bajawa III elementary school cluster, selected through random sampling and divided into experimental and control groups. Sound-symbol understanding and language skills were measured using validated test instruments. Results: The results show that the developed interactive multimedia was feasible for classroom use based on assessments by the media and subject-matter experts. The average gain score for sound symbol understanding in the experimental group was 0.62, which falls into the moderate category, while the average gain score for language skills was 0.79, which falls into the high category. Conclusions: These findings indicate that Adobe Flash-assisted interactive multimedia was successfully developed and is both feasible and effective for improving students’ sound symbol understanding and language skills.